Non-hydrophobized perlite renders for repair and thermal insulation purposes: Influence of different binders on their properties and durability. (10th December 2020) - Vyšvařil, Martin; Pavlíková, Milena; Záleská, Martina; Pivák, Adam; Žižlavský, Tomáš; Rovnaníková, Pavla; Bayer, Patrik; Pavlík, Zbyšek
Highlights: Non-hydrophobized perlite lightened renders based on different binders. A wide set of structural, mechanical, thermal, hygric, and durability properties. The use of perlite positively affects functional properties and durability of renders. Lime- and natural hydraulic lime-based thermal insulation and repair mortars. Cement-lime renders are unadvisable for repair of historical buildings. Abstract: To meet today's increasing requirements on the quality of life and thus indoor air climate, new advanced construction materials are under research and development. Specific issue represents repair and renewal of old or historically valuable buildings, where the newly applied materials must be compatible with those originally used in the past. Taking into consideration the necessity to decrease the energy consumption of existing buildings with valuable aesthetic facades and appearance, use of repair renders with improved thermal insulation performance represents acceptable solution to adopt the present building stock to actual thermal requirements. In this paper, complex characterization of non-hydrophobized lightweight renders designed at once for repair and thermal insulation purposes was performed. In composition of designed materials, silica sand was partially or fully replaced with expanded perlite of the similar grain size distribution, whereas the workability of fresh renders was maintained on the same level. Among broad experimental campaign, structural parameters, moisture and heat transport and storage properties, and mechanical parameters of the hardened renders were assessed in dependence on time of samples maturing. Frost resistance test was conducted to characterize renders durability. The use of lime and natural hydraulic lime in composition of perlite lightened mortars enabled to meet all the criteria on rendering and masonry mortars taking into consideration their functionality, compatibility, durability and thermal insulation performance. These mortars well found usable for repair of historical masonry and even in conservation of heritage protected buildings. On the other hand, the cement-lime renders were found to be incompatible, too rigid and less permeable both for water and water vapor than required by culture heritage authorities, related technical standards and directives for repair renders. Nevertheless, these can find use in the construction of new buildings as thermal insulation and general purpose mortars.